REAL ESTATE INVESTMENT TRUST DALAM KERANGKA HUKUM PASAR MODAL INDONESIA - Paripurna P Sugarda (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2007)
AbstractThe Development of property business investment is entering new era. This can be seen with the new investment, Real Estate Investment Trust (REIT), which can be offered to investor in capital market. The emergence of new investment cause capital needs closely inter-link between property industry and capital market, whereby traditionally, banking industry dominated before. Property market will be more efficient, fair, accountable. It is not only dominated by only some participants/exclusives but also opened investment opportunities for middle or small investor. A part from that, the tendency of banking industries is very selective to lend fund and high interest, open to grow up this investment opportunity. Also, Indonesia is judged as one of high potential countries to grow up this property trust because of high property grow up. Regard that condition, this paper demonstrates law relation between parties in REIT and how rules of Law of Republic Indonesia Number 8 Year 1995 concerning Capital Market can accomodate the REIT implementation all at once as ‘Law Umbrella’ in Indonesia Law.